2018
DOI: 10.1111/ppl.12870
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of molecular mechanisms and physiochemical characters in wild and cultivated soybeans against invasion by the pathogenic Fusarium oxysporum Schltdl

Abstract: Cultivated soybean (Glycine max) was derived from the wild soybean (Glycine soja), which has genetic resources that can be critically important for improving plant stress resistance. However, little information is available pertaining to the molecular and physiochemical comparison between the cultivated and wild soybeans in response to the pathogenic Fusarium oxysporum Schltdl. In this study, we first used comparative phenotypic and paraffin section analyses to indicate that wild soybean is indeed more resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
(82 reference statements)
2
9
0
Order By: Relevance
“…Seven DEGs were selected for validation of the RNA-seq data using quantitative reverse transcription polymerase chain reaction (RT-qPCR) (Supplementary Table 3). The RT-qPCR data for these genes were consistent with the RNA-seq results from the four group samples, which indicated a high degree of reproducibility between the DEG fold changes assayed using RNA-seq and the expression profiles revealed by RT-qPCR (Chang et al, 2018). …”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Seven DEGs were selected for validation of the RNA-seq data using quantitative reverse transcription polymerase chain reaction (RT-qPCR) (Supplementary Table 3). The RT-qPCR data for these genes were consistent with the RNA-seq results from the four group samples, which indicated a high degree of reproducibility between the DEG fold changes assayed using RNA-seq and the expression profiles revealed by RT-qPCR (Chang et al, 2018). …”
Section: Resultssupporting
confidence: 71%
“…The average error rate of the sequences ranged from 0.0128–0.0132%, and more than 96% of the bases had error rates < 0.1% (Supplementary Table 2) (Chang et al, 2018). The short read sequences were blasted against the soybean reference genome (Wm82.a2.v1), and the total mapping rates ranged from 54.96% to 74.76%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAseq analysis of Glycine max infected with both pathogenic and non-pathogenic strains of F. oxysporum identified over-representation of defense-related genes corresponding to necrosis in resistant interactions (Lanubile et al, 2015). RNAseq was carried out to understand the molecular differences in defense responses between cultivated and wild species of Glycine max against the pathogenic F. oxysporum Schltdl (Chang et al, 2019). That study identified the role of secondary metabolites and plant hormones in wild-type germplasm that could be adapted into cultivated species for enhanced resistance.…”
Section: Using Genomics To Understand the Basics Of Plant–pathogen Inmentioning
confidence: 99%